ADHD: science, stigma and service implications. (24th May 2018) - Gavin, B.; McNicholas, F.
Abstract : We are delighted to dedicate an edition of the Irish Journal of Psychological Medicine to the topic of attention-deficit hyperactivity disorder (ADHD). ADHD accounts for the majority of clinical presentations to Child and Adolescent Mental Health Services, both in terms of new assessments and ongoing attendances. Papers presented in this edition reflect on the evolving construct of ADHD, drawing from science, clinical practice and public opinion. Current and evidenced-based assessment and treatment practice guidelines are reviewed. International longitudinal studies allow us to understand the personal and societal cost, which can persist for many years post-diagnosis. Despite continuation to adulthood in many young people, follow on adult services are lacking. It is fitting that submissions, by way of personal reflections and opinion pieces, are also included from adult colleagues as they reflect on their experiences in this area. Given the recent development of a national clinical programme in ADHD in Ireland, coupled with a growing evidence for effective interventions, it is hoped that this special edition will highlight the need for appropriate and accessible ADHD treatments across the lifespan.